Examining the significance of civil society in augmenting and empowering youth; within the context of Iraqi Kurdistan - Hussein, Jamal Mohammed Ameen; Jalal Nori, Abdulwahed (2023)
This scholarly abstract delves into the pivotal role of civil society organisations in the advancement and empowerment of youth in the region of Iraqi Kurdistan. In the dynamic socio-political landscape of the Kurdistan region, civil society entities have emerged as vital agents of change and progress. This article explores the multifaceted strategies and initiatives undertaken by these organisations to address the diverse needs and aspirations of Kurdish youth. It delves into the challenges faced and the innovative approaches employed, shedding light on the transformational potential that civil society can offer in nurturing a more resilient and empowered youth population. This study uses historical, descriptive, and case studies to establish that youth CSOs play a vital role in the democratisation and political process in Iraqi Kurdistan. Given the serious dependence of youth CSOs on freedom for their operations, by scrutinising the intricate interplay between civil society and youth development, this article aims to provide valuable insights for policymakers, scholars, and practitioners invested in the sustainable growth and prosperity of youth in Iraqi Kurdistan.